2017
DOI: 10.1016/j.ecolmodel.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

The role of bivalves in the Balgzand: First steps on an integrated modelling approach

Abstract: a b s t r a c tThe present paper describes a process oriented modelling tool that integrates physical, biogeochemical, ecological and physiological factors governing bivalve populated marine ecosystems. This modelling tool is the result of the coupling between an individual-based population model for bivalves (based on the Dynamic Energy Budgets theory, DEB) and a hydrodynamic/biogeochemical model (MOHID Water Modelling System). The model was implemented in the Balgzand area (Wadden Sea, The Netherlands) in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The models include energy reserves and structural tissue (e.g., shells) as separate state variables, allowing for a mechanistic description of energy distribution and conservation and varying C:N:P ratios within the individual. There are a few examples of DEB models integrated into in biogeochemical-hydrodynamic models used to study the effects of bivalves on nutrient cycles in coastal areas (Maar et al, 2009;Grangeré et al, 2010;Ren et al, 2010;Saraiva et al, 2017), but their more extensive use in this context is probably hampered by their complexity (Brown et al, 2004a;Filgueira et al, 2011), and because they require parameters that are difficult to derive from commonly measured rates (van der Meer, 2006).…”
Section: Biomass Model Types and State Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The models include energy reserves and structural tissue (e.g., shells) as separate state variables, allowing for a mechanistic description of energy distribution and conservation and varying C:N:P ratios within the individual. There are a few examples of DEB models integrated into in biogeochemical-hydrodynamic models used to study the effects of bivalves on nutrient cycles in coastal areas (Maar et al, 2009;Grangeré et al, 2010;Ren et al, 2010;Saraiva et al, 2017), but their more extensive use in this context is probably hampered by their complexity (Brown et al, 2004a;Filgueira et al, 2011), and because they require parameters that are difficult to derive from commonly measured rates (van der Meer, 2006).…”
Section: Biomass Model Types and State Variablesmentioning
confidence: 99%
“…Supply and successful establishment of pelagic larvae may be an important factor limiting species occurrence and biomass especially in enclosed coastal areas (Barnes, 1994;Palmer et al, 1996). Saraiva et al (2017) showed the importance of larval recruitment and survival for blue mussels Mytilus edulis in the Wadden Sea using a DEB model coupled to a 3D hydrodynamic-biogeochemical model.…”
Section: Biomass Model Types and State Variablesmentioning
confidence: 99%
“…The versatility and flexibility of the MOHID Water eases its implementation in any type of system and to accomplish different modelling requirements depending on the objectives of the work to be performed. Indeed, in the last four years the MOHID Water was applied in multiple studies worldwide, namely in Canada [13], Colombia [14,15], Brazil [16], Argentina [17,18], Uruguay [19], Holland [20], France [21], Spain [22], Croatia [23], Australia [24,25], Malaysia [26] and Korea [27]. In Portugal, this model has been implemented in the entire Portuguese coast [28][29][30] and in all main estuaries [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, marine mussels, which have long served as DEB theory model species 14 , are predominantly modelled under relatively stable subtidal conditions. While many DEB model applications have incorporated natural environmental variability, successfully capturing organisms’ physiological responses 15 17 , less attention has been given to explicitly testing model performance under steep gradients of environmental variability. Ignoring environmental variability can reduce the predictive power of energy budget models, and variability deserves special consideration when working with taxa subject to wide fluctuations in food and temperature, as recently highlighted for terrestrial and semi-aquatic species 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%